Viral etiology of medically attended influenza‐like illnesses in children less than five years old in Suzhou, China, 2011–2014. Issue 8 (2nd February 2016) - Wang, Dan; Chen, Liling; Ding, Yunfang; Zhang, Jun; Hua, Jun; Geng, Qian; Ya, Xuerong; Zeng, Shanshan; Wu, Jing; Jiang, Yanwei; Zhang, Tao; Zhao, Genming
Abstract : Limited information is available on the non‐influenza etiology and epidemiology of influenza‐like illness (ILI) in China. From April 2011 to March 2014, we collected oropharyngeal swabs from children less than 5 years of age with symptoms of ILI who presented to the outpatient departments of Suzhou University Affiliated Children's Hospital (SCH). We used reverse transcription polymerase chain reaction (rt‐PCR) or PCR to detect 11 respiratory viruses. Among 3, 662 enrolled ILI patients, 1, 292 (35.3%) tested positive for at least one virus. Influenza virus (16.9%) was detected most frequently (influenza A 7.4%, influenza B 9.5%), followed by respiratory syncytial virus (RSV) (5.6%), parainfluenza virus (PIV) types 1–4 (4.8%), human bocavirus (HBoV) (3.8%), human metapneumovirus (HMPV) (3.5%), and adenovirus (ADV) (3.0%). Co‐infections were identified in 108 (2.9%) patients. Influenza virus predominantly circulated in January–March and June–July. The 2013–2014 winter peaks of RSV and influenza overlapped. Compared with other virus positive cases, influenza positive cases were more likely to present with febrile seizure, and RSV positive cases were more likely to present with cough and wheezing, and were most frequently diagnosed with pneumonia. These data provide a better understanding of the viral etiology of ILI among children less than 5 years of age in Suzhou, China. Influenza is not only the most frequently identified pathogen but it is also the only vaccine preventable illness among the 11 pathogens tested. Such findings suggest the potential value of exploring value of influenza vaccination among this influenza vaccination target group. J. Med. Virol. 88:1334–1340, 2016 . © 2016 Wiley Periodicals, Inc.